Rancang Bangun Mokodame : Monitoring Ekosistem Udang Vaname (Litopenaeus vannamei) pada AQUARIUM dengan SISTEM Internet of Things - Hendra Prayitno; Rahmat Hidayat; Ibrahim Ibrahim (Peneliti.net, 2022)
The rapid development of shrimp farming has created problems. One of the main problems in shrimp ponds is the quality of pond water which must be in accordance with the needs of shrimp life, the monitoring process is usually done manually. Internet of Things (IoT) based shrimp pond water quality monitoring is made to make monitoring easier. The device has 2 systems, namely 3 inputs in the form of a temperature sensor, a pH sensor and a salinity sensor, while the output part is an LCD (Liquid Crystal Display), Blynk, water pump, dc fan and dc motor controlled by Arduino Mega 2560. The process of sending data to Blynk uses NodeMcu. Test analysis is done by taking samples from different values. The formula y=a+bx is used in sample processing using linear regression. The average accuracy of each temperature sensor = 99.10%, pH sensor = 99.09% and salinity sensor = 90.98%. The error of each temperature sensor = 0.90%, pH sensor = 0.91% and salinity sensor = 9.12%.